2017
DOI: 10.1051/kmae/2017032
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical thresholds in the distribution of fish species among French lakes

Abstract: -The management of lakes requires the definition of physico-chemical thresholds to be used for ecosystem preservation or restoration. According to the European Water Framework Directive, the limits between physico-chemical quality classes must be set consistently with biological quality elements. One way to do this consists in analyzing the response of aquatic communities to environmental gradients across monitoring sites and in identifying ecological community thresholds, i.e. zones in the gradients where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 69 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…The threshold values indicate where the first substantial change in fish community composition occurs in relation to increasing urban and agricultural land use. We generated 1,000 trees for each RF model and used default constrained permutations with correlation threshold of 0.5 to reduce the influence of multicollinearity (Ellis et al., 2012; Roubeix et al., 2017). Relative abundance data was arcsine square root transformed to meet statistical requirements, whereas GF are invariant to monotonic transformations of the explanatory variables (Wagenhoff et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold values indicate where the first substantial change in fish community composition occurs in relation to increasing urban and agricultural land use. We generated 1,000 trees for each RF model and used default constrained permutations with correlation threshold of 0.5 to reduce the influence of multicollinearity (Ellis et al., 2012; Roubeix et al., 2017). Relative abundance data was arcsine square root transformed to meet statistical requirements, whereas GF are invariant to monotonic transformations of the explanatory variables (Wagenhoff et al., 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The threshold values indicate where the first substantial change in fish community composition occurs in relation to increasing urban and agricultural land use. We generated 1,000 trees for each RF model and used default constrained permutations with correlation threshold of 0.5 to reduce the influence of multicollinearity (Ellis et al, 2012;Roubeix et al, 2017).…”
Section: Quantifying Land Use Thresholds In Fish Community Compositionmentioning
confidence: 99%
“…In particular, environmental agencies and stakeholders are most interested in high temperatures, which can cause mortality and thermal stress (Caissie et al, 2001;Davies-Colley et al, 2013). In fact, in France maximum annual water temperature is the main parameter determining the composition of the fish community in lakes (Roubeix et al, 2017). However, low temperatures are important too.…”
Section: Summer and Winter Surface Temperaturesmentioning
confidence: 99%
“…A total of 153 surveys in Mayotte, and 262 in Reunion, were included in these analyses due to missing data. The average R 2 was 0.19 in Mayotte and 0.28 in Reunion, which means that the variance in species abundances was moderately explained by environmental variables in both islands (Roubeix et al., 2017). The four taxa for which the total deviance was best explained by GF were Ophieleotris cf.…”
Section: Resultsmentioning
confidence: 99%
“…This latter advantage appeared particularly relevant in the context of our study as data preview revealed nonlinear relationships between taxa abundances and several environmental variables. To limit the bias caused by rare species, GF analyses were performed on species occurring in more than 3.5% of the surveys only (Roubeix et al., 2017).…”
Section: Methodsmentioning
confidence: 99%